Assessing informed consent in medical malpractice cases associated with different surgical fields referring to Tehran's Commission of Forensic Medicine, 2017 - Mostafazadeh, Babak; Najari, Fares; Emamhadi, Mohammad Ali; ghaedi, ghasem (Novelty in Biomedicine, 2020)
Background: Increasing the number of complaints against medical staff emphasizes the need for physicians to be more familiar with legal issues before and during providing medical services to the patient. Signing the informed consent form before medical practices and informing the patient of all possible outcomes can cause mental health and better collaboration of patients as well as increase the physician's self-confidence to provide better services. The current study aimed at determining the status of standard informed consent in medical cases related to different surgical fields referring to Tehran's Commission of Forensic Medicine during the first quarter of 2017. Materials and Methods: In the current descriptive, cross-sectional study, the cases of medical malpractice related to different surgical fields referring to Tehran's Commission of Forensic Medicine in the first quarter of 2017 were investigated. Data were analyzed with SPSS version 16. Results: In the current study, 124 cases of complaints against the medical staff of the surgical fields were examined. Based on the obtained data, the age and specialty of physicians, faculty status, and type of treatment center were effective in obtaining standard informed consent, and the highest percentage of allegations against the charge was related to cases attempted to obtain informed consent. Conclusion: Obtaining the standard consent can significantly improve the patient-physician relationships and reduce the rate of medical malpractice complaints.